Nutrients cause grassland biomass to outpace herbivory - Borer, E. T.; Harpole, W. S.; Adler, P. B.; Arnillas, C. A.; Bugalho, M. N.; Cadotte, M. W.; Caldeira, M. C.; Campana, S.; Dickman, C. R.; Dickson, T. L.; Donohue, I.; Eskelinen, A.; et al. (Springer Nature, 2020)
Human activities are transforming grassland biomass via changing climate, elemental nutrients, and herbivory. Theory predicts that food-limited herbivores will consume any additional biomass stimulated by nutrient inputs (‘consumer-controlled’). Alternatively, nutrient supply is predicted to increase biomass where herbivores alter community composition or are limited by factors other than food (‘resource-controlled’). Using an experiment replicated in 58 grasslands spanning six continents, we show that nutrient addition and vertebrate herbivore exclusion each caused sustained increases in aboveground live biomass over a decade, but consumer control was weak. However, at sites with high vertebrate grazing intensity or domestic livestock, herbivores consumed the additional fertilization-induced biomass, supporting the consumer-controlled prediction. Herbivores most effectively reduced the additional live biomass at sites with low precipitation or high ambient soil nitrogen. Overall, these experimental results suggest that grassland biomass will outstrip wild herbivore control as human activities increase elemental nutrient supply, with widespread consequences for grazing and fire risk.